(NkONTROLX KA^ESTWA POWERHNOSTNYH WOD (B:s (Nu^EBNOE POSOBIE (B/s - (NoRLOW(B, (NwADIM gEORGIEWI^s; (NlENINGRADSKIJ GIDROMETEOROLOGI^ESKIJ INSTITUTs ((NlENINGRAD (B:s (NlENINGRADSKOGO POLITEHNI^ESKOGO IN(B-(NTA(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 136-137 (22 (NNAZW(B.)s
(NnA OBL(B. (NAWT(B.: (Nw(B.(Ng(B. (NoRLOWs
Keywords: (NwODY POWERHNOSTNYE (B- (NkA^ESTWOs; (NwODY POWERHNOSTNYE (B- (NoHRANAs